The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2018jf004766
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Sediments in Chilean Rivers Reveal Low Postseismic Erosion After the Maule Earthquake (Mw 8.8) During a Severe Drought

Abstract: We address the question of whether all large‐magnitude earthquakes produce an erosion peak in the subaerial components of fluvial catchments. We evaluate the sediment flux response to the Maule earthquake in the Chilean Andes (Mw 8.8) using daily suspended sediment records from 31 river gauges. The catchments cover drainage areas of 350 to around 10,000 km2, including a wide range of topographic slopes and vegetation cover of the Andean western flank. We compare the 3‐ to 8‐year postseismic record of sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 100 publications
(183 reference statements)
1
18
1
Order By: Relevance
“…The export of OC during the post-seismic period depends strongly on the fine sediment export rate (Hovius et al, 2011;Tolorza et al, 2019;Wang et al, 2015;Wang et al, 2016). A few examples have shown that, in wet climates, suspended load fluxes after a large earthquake are characterized by a rapid increase directly after the seismic event, which is sustained for less than a decade, before returning to background levels (Hovius et al, 2011).…”
Section: Comparison To Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The export of OC during the post-seismic period depends strongly on the fine sediment export rate (Hovius et al, 2011;Tolorza et al, 2019;Wang et al, 2015;Wang et al, 2016). A few examples have shown that, in wet climates, suspended load fluxes after a large earthquake are characterized by a rapid increase directly after the seismic event, which is sustained for less than a decade, before returning to background levels (Hovius et al, 2011).…”
Section: Comparison To Previous Workmentioning
confidence: 99%
“…The export of OC from mountain river catchments is linked to that of fine clastic sediment (Galy et al, 2015;Hilton et al, 2012). Following widespread earthquake-triggered landsliding, fine sediment can be evacuated as fluvial suspended load within a decade in wet, subtropical settings such as Taiwan (Dadson et al, 2004;Hovius et al, 2011), or over several decades in more arid locations (Tolorza et al, 2019;Wang et al, 2015). The total landslide-derived sediment volume, including coarse material which can be mobilized by debris flows and transported as bed load, may take decades to centuries to export (Croissant et al, 2017;Fan et al, 2018;Yanites et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Application of RFM to catchments in Minnesota showed that the offset was primarily controlled by land use, whereas the shape and slope were controlled by factors related to the geomorphic characteristics and geologic history of the basin (i.e., near-channel relief, channel gradient, and the number of lakes within the channelfloodplain corridor) (Vaughan et al, 2017). Tolorza et al (2019) used a similar technique to identify physical factors that regulate changes in suspended sediment concentrations following a large tectonic event.…”
Section: Sediment Rating Curvesmentioning
confidence: 99%
“…Prolonged shifts in SRCs can also occur in response to major land-use changes and (Warrick et al, 2013) and extreme hydrologic events (Gray, 2018;Gray et al, 2015). Chile (Tolorza et al, 2019). This suggests that SRCs may respond to punctuated sediment loading, whether from tectonic activity or intensive timber harvest activities, in similar ways.…”
Section: Random Forest Modelingmentioning
confidence: 99%
See 1 more Smart Citation